Morbidity profile among patients attending allopathic healthcare facilities in Kalutara District, Sri Lanka - Naveen de Soysa; Udayi Gunawardana; Supipi Dissanayake Gunawardana; Padmal de Silva (Journal of the College of Community Physicians)
Introduction: To achieve Universal Health Coverage (UHC), access to quality health services without financial hardship is essential. Although morbidity profiles influence healthcare utilization, national-level morbidity profiles of outpatients are not regularly reported, hindering the assessment of UHC progress. Objectives: To describe the morbidity profile of patients attending out-patient care in all categories of healthcare facilities practising Western medicine in Kalutara District in 2019 Methods: A descriptive cross-sectional study with an analytical component was conducted on 1,005 outpatients in healthcare institutions practising Western medicine in the Kalutara District. One-day survey via an interviewer-administered questionnaire was done with two-staged stratified-cluster sampling technique. Patients seeking medical certificates/check-ups or living outside the district were excluded. Results: The sample was 1,005. The commonest groups seeking care were more than 50 years (n=339; 33.7%), females (n=570; 56.7%), Sinhalese (n=890; 88.5%) and with the highest education level between grade 6 to GCE Ordinary Level (n=521; 51.8%) visiting outpatient departments (OPD) in contrast to general practitioners (GP) where less than 18 years (31.3%) and males (52.7%) were the commonest. The commonest symptom category (39.1%) was respiratory in all facilities. More than half (57.6%) sought treatment within the first three days of illness with early presentation to GP. Nearly 50% had comorbidities with the commonest being cardiovascular diseases. More than two fifths (44.2%) had some kind of disability. Conclusions: Except for a few similarities, the morbidity profile showed variations across different levels of healthcare facilities with notable deviations in relation to age and gender when GP settings were concerned.